Self-regulation, stress appraisal, and esport action performance - Trotter, Michael G.; Obine, Emmanuel A. C.; Sharpe, Benjamin T. (Frontiers in Psychology, 2023)
Electronic sport has seen substantial growth in market value and popularity in the last 10 years. With this growth has come the pursuit of elite esports performance, especially from a psychological perspective. This study aimed to investigate potential variations in self-regulation levels among athletes of different levels (national vs. student), compare the self-regulation profiles of CS:GO players in the current study to an international sample of e’athletes and to assess the predictive capacity of self-regulation on performance outcomes. A total of 53 esports athletes (student competitors, n = 27 and national-level CS:GO competitors, n = 26), participated in an experiment exploring self-regulation, DRES, and action performance. Furthermore, analysis comparing our collective findings against a larger global sample of e’athletes (n = 993) was conducted. Results demonstrated that CS:GO players who displayed higher levels of self-regulation tended to perceive stressful situations as challenges, consequently showcasing superior accuracy and time trial performance. In contrast, individuals with lower self-regulation tended to perceive such situations as threats, which correlated with less favorable performance outcomes. On a broader scale, the study observed that CS:GO competitors generally exhibited lower levels of self-regulation when compared to the larger global sample. Furthermore, self-regulation was identified as a mediating variable in the relationship between stress appraisal and performance, suggesting that improved self-regulation skills can lead to enhanced accuracy and quicker time trial performance. This may imply that competitors with greater self-regulatory abilities perceive themselves as having more personal resources, enabling them to effectively assess challenging situations and employ problem-focused coping strategies. Overall, this research underscores the significance of self-regulation in optimizing esports performance, while providing valuable insights for player development, action performance, and overall outcomes in the field.